2007
DOI: 10.1172/jci29159
|View full text |Cite
|
Sign up to set email alerts
|

Myd88-dependent positioning of Ptgs2-expressing stromal cells maintains colonic epithelial proliferation during injury

Abstract: We identified cellular and molecular mechanisms within the stem cell niche that control the activity of colonic epithelial progenitors (ColEPs) during injury. Here, we show that while WT mice maintained ColEP proliferation in the rectum following injury with dextran sodium sulfate, similarly treated Myd88 -/-(TLR signaling-deficient) and prostaglandin-endoperoxide synthase 2 -/-(Ptgs2 -/-) mice exhibited a profound inhibition of epithelial proliferation and cellular organization within rectal crypts. Exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
205
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(220 citation statements)
references
References 44 publications
12
205
0
3
Order By: Relevance
“…Thus, efficient wound healing appears to be Myd88-independent for acute colonic mucosal injuries. One possible explanation for the difference of the two systems is that DSS inhibits epithelial proliferation that requires both TLR and prostaglandins to rescue it in WT mice (15). This finding is similar to skin, where Myd88 signaling was required for proper wound healing only when punch biopsies were inoculated with pathogenic microbes (20).…”
Section: Efficient Wound Healing Did Not Require Neutrophils or Tlr-smentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, efficient wound healing appears to be Myd88-independent for acute colonic mucosal injuries. One possible explanation for the difference of the two systems is that DSS inhibits epithelial proliferation that requires both TLR and prostaglandins to rescue it in WT mice (15). This finding is similar to skin, where Myd88 signaling was required for proper wound healing only when punch biopsies were inoculated with pathogenic microbes (20).…”
Section: Efficient Wound Healing Did Not Require Neutrophils or Tlr-smentioning
confidence: 90%
“…Recent studies have suggested that colonic epithelial stem cells are strongly influenced by their local stromal microenvironment and Myd88-dependent Toll-like receptor signaling during mucosal injury (7,15). We quantified the major stromal cell types in both the wound bed and adjacent crypt areas of WT and Myd88 Ϫ/Ϫ mice.…”
Section: Efficient Wound Healing Did Not Require Neutrophils or Tlr-smentioning
confidence: 99%
“…Finally, although Myd88 -/-mice showed impaired regenerative IEC proliferation after DSSinduced epithelial injury [42,45], it is not clear whether this effect is due to defective MyD88 signaling in epithelial cells themselves or in other mucosal cells. Indeed, the proliferative IEC response after DSS injury is thought to rely on MyD88-dependent positioning of activated macrophages and COX2-producing stromal cells near the crypt base [50,51]. However, IEC-intrinsic MyD88 signaling could still play a role in these events, because bone marrow transfer experiments have suggested that recruitment and activation of macrophages depends on TLR4 signaling in IECs [52].…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actimentioning
confidence: 99%
“…Identifying these MyD88-dependent processes will be an exciting avenue for future research. It would also be important to investigate whether the mechanism described by Brown et al (3) operates in other parts of the colon and the small intestine.…”
Section: Innate Immune Recognition Of the Commensal Microflora As A Cmentioning
confidence: 99%